Multi-resonance thermal activation delayed fluorescence material based on peripheral heavy atom substitution and application of multi-resonance thermal activation delayed fluorescence material in organic electroluminescent device

By introducing heavy atoms to increase SOCs in the periphery of the multi-resonance framework of MR-TADF materials, the problems of slow kRISC and aggregation-induced quenching effect are solved, and organic electroluminescent devices with high efficiency and high color purity are achieved, which promotes the OLED technology universal.

CN119143789AActive Publication Date: 2024-12-17JILIN UNIVERSITY

Patent Information

Application Number
CN202411298336.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-17
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

In existing MR-TADF materials, the slower kRISC, triplet exciton annihilation and aggregation-induced quenching effects between molecules have serious effects, resulting in serious roll-off of electroluminescent devices at high brightness.

Method used

The spin-orbit coupling (SOC) of the system is increased by introducing heavy atoms (such as sulfur or selenium) around the multi-resonance framework, thereby improving the inter-coordinated crossing rate and avoiding the accumulation and quenching of triplet excitons. Maintain narrow half-maximum width of the emission spectrum.

Benefits of technology

The organic electroluminescent device with high efficiency, high color purity and low efficiency roll-off has been achieved, and the problem of efficiency attenuation and deterioration of color purity at high brightness by MR-TADF materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143789A_ABST
    Figure CN119143789A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-resonance thermal activation delayed fluorescence material based on peripheral heavy atom substitution and application of the multi-resonance thermal activation delayed fluorescence material in an organic light-emitting device, and belongs to the technical field of organic light-emitting devices. According to the multi-resonance thermal activation delayed fluorescence material based on peripheral heavy atom substitution, heavy atoms are introduced to the periphery of a multi-resonance framework to increase spin-orbit coupling of a system, the reverse intersystem crossing rate from a triplet state to a singlet state is increased, and efficiency roll-off is inhibited; meanwhile, the structural relaxation of molecules is not increased, the multi-resonance characteristic of the whole system is influenced, and the narrow half-peak width and high luminous efficiency of the system are kept. The prepared organic electroluminescent device overcomes the defect that the efficiency attenuation of the MR-TADF material is serious under high brightness and the like, the organic electroluminescent device with high efficiency, high color purity and low efficiency roll-off is realized, and the organic electroluminescent device plays an important role in promoting further popularization of the organic electroluminescent technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of organic electroluminescent devices, and in particular relates to a multi-resonance thermally activated delayed fluorescence material based on peripheral heavy atom substitution and an application thereof in organic electroluminescent devices. Background Art

[0002] Organic Light Emission Diodes (OLED) is a new type of display technology with the advantages of high brightness, fast response, wide viewing angle, simple process, and flexibility. It has made great progress in full-color display and lighting application technology and has become a hot trend in current industrialization. In recent years, the third-generation luminescent material-Thermal-Activated Delayed Fluorescence (TADF) material has been widely developed and applied in electronic devices because it can effectively utilize triplet excitons, and has become a frontier research hotspot in the field of luminescent materials. However, most of the current TADF materials adopt a donor-acceptor structure. The vibration coupling between the ground state and the excited state and the relaxation of the excited state structure cause the half-peak width (full-width at half maximum, FWHM>70nm) of its emission spectrum to be wide, which cannot meet the technical requirements of high color purity of full-color display technology. Although the device structure using filters or optical microcavities can meet the display requirements for color purity, this not only makes the device structure complex, but also causes a large energy loss, which is not conducive to energy saving and environmental protection requirements.

[0003] In recent years, new TADF materials with boron / nitrogen multiple resonance (MR) effect have been reported one after another, which can maximally suppress the bonding / antibonding characteristics, structural relaxation and vibration coupling of the excited state, thereby achieving narrow-band emission characteristics, and at the same time have a large oscillator strength (f) and the resulting high fluorescence quantum yield (PLQY), which is conducive to achieving high color purity and high luminescence efficiency. However, the reverse intersystem crossing (RISC) rate (k RISC For 10 3 -10 4 s -1 ) is slower, usually leading to the accumulation of triplet excitons and subsequent exciton annihilation, resulting in severe efficiency roll-off at high brightness. -2When the efficiency is even reduced to less than half of the maximum EQE value, it hinders their commercial application potential. In addition, the boron / nitrogen multiple resonance system compound has a relatively rigid planar structure, the interaction between molecules is strong, and it is easy to aggregate. When preparing electroluminescent devices, it is easy to produce aggregation-induced quenching effect, which further leads to the deterioration of the luminescent performance of the material and the color purity of the device. Therefore, the development of new organic light-emitting materials and electroluminescent devices with high efficiency, high color purity, and high efficiency at high brightness is of great significance for practical applications and plays an important role in promoting the further popularization of OLEDs technology. Summary of the invention

[0004] The technical problem to be solved by the present invention is that k RISC The slow quenching effect caused by triplet exciton annihilation and molecular aggregation leads to serious efficiency roll-off of electroluminescent devices at high brightness. RISC The energy level difference with the single triplet state (ΔE ST ) is related to spin-orbit coupling (SOC), and the ΔE of the MR-TADF molecule ST Between 0.1eV and 0.2eV. Therefore, if we want to increase k RISC , it is necessary to increase the SOC of the system. It is generally believed that the greater the nuclear charge number of the atomic nuclei contained in the system, the higher the SOC intensity, and the higher the possibility of electron spin flipping, which is the "heavy atom effect". However, the introduction of heavy atoms (sulfur or selenium atoms) on the multi-resonance skeleton will increase the structural relaxation of the molecule, increase the half-width of the MR-TADF molecule (FWHM>50nm), and affect the color purity of the molecule. In view of the existing problems, the present invention provides a simple and effective strategy to improve the RISC rate of MR-TADF materials without affecting the color purity, that is, by introducing heavy atoms on the periphery of the multi-resonance skeleton to increase the SOC of the system, while not increasing the structural relaxation of the molecule, affecting the multi-resonance characteristics of the system, maintaining the narrow half-width of the system, and overcoming the shortcomings of the MR-TADF material under high brightness, such as severe attenuation of device efficiency and widening of the half-width.

[0005] The multi-resonance thermally activated delayed fluorescence material based on peripheral heavy atom substitution described in the present invention has a structural formula as shown below:

[0006]

[0007] Wherein R is sulfur (S) or selenium (Se);

[0008] Furthermore, the multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution described in the present invention has a structural formula as shown in one of the following:

[0009]

[0010] The organic electroluminescent device prepared by the product of the present invention is composed of a cathode, an anode and one or more organic layers between the two electrodes, at least one of the organic layers is an organic light-emitting layer, and the organic light-emitting layer is composed of a multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution prepared by the present invention as a doped guest material and PhCzBCz as a doped host material, and the mass doping ratio of the guest material is 2-5%. The electroluminescent device can be used to prepare an organic electroluminescent display or an organic electroluminescent lighting source.

[0011] Furthermore, an embodiment of the present invention provides an organic electroluminescent device, which is composed of a transparent substrate, an ITO conductive film (anode), a hole injection layer (HATCN), a hole transport layer (TAPC), an exciton blocking layer (TCTA and mCP), a light-emitting layer, an electron transport layer (TmPyPB), an electron injection layer (LiF) and a cathode layer (Al) from bottom to top, and all functional layers can be prepared by a vacuum evaporation film-forming process.

[0012] Preferably, some organic compounds used in the device are commercially available or prepared according to known literature or patents, and the molecular structure is shown below:

[0013]

[0014] The beneficial effects of the present invention are:

[0015] The multi-resonance thermally activated delayed fluorescence material based on peripheral heavy atom substitution of the present invention has high luminescence efficiency, high reverse intersystem crossing rate and narrow half-peak width. RISCThe quenching of triplet excitons is relatively slow, resulting in the accumulation of triplet excitons and subsequent exciton annihilation, including the quenching of triplet excitons and triplet excitons (TTA), the quenching of triplet excitons and singlet excitons (TSA), and the quenching between triplet excitons and polarons (TPA). These quenching processes are the main reason for the efficiency roll-off of MR-TADF devices. If you want to achieve a low-efficiency roll-off device, you must find a way to weaken the accumulation of triplet excitons, avoid the quenching of triplet excitons, and increase the movement rate of triplet excitons so that they are converted into singlet excitons to produce delayed fluorescence. The present invention provides a simple and effective strategy to improve the RISC of MR-TADF materials without affecting the color purity, that is, by introducing heavy atoms on the periphery of the multi-resonance skeleton to increase the SOC of the system, while not affecting the multi-resonance characteristics of the system, and maintaining the narrow half-peak width of the system. The organic electroluminescent device prepared in this way overcomes the shortcomings of MR-TADF materials such as severe efficiency attenuation at high brightness, and realizes an organic electroluminescent device with high efficiency, high color purity and low efficiency roll-off, which plays an important role in promoting the further popularization of organic electroluminescent technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 : Schematic diagram of the structure of the organic electroluminescent device prepared by the present invention, in which 1 is a transparent substrate, 2 is an ITO anode, 3 is a hole injection layer, 4 is a hole transport layer, 5 is an exciton blocking layer, 6 is an organic light-emitting layer, 7 is an electron transport layer, 8 is an electron injection layer, and 9 is a cathode.

[0017] Figure 2 :UV (Abs.), fluorescence (FL.) and low-temperature phosphorescence (Phos.) spectra of compound BN-1; the maximum absorption peak is 468nm, the main emission peak is at 483nm, which is blue-green light emission, and the half-peak width is 22nm; the energies of S1 and T1 are calculated to be 2.57eV and 2.40eV respectively through the main peak positions of fluorescence and low-temperature phosphorescence, and the ΔE of the two molecules can be calculated ST It is 0.17eV.

[0018] Figure 3 :UV, fluorescence and low-temperature phosphorescence spectra of compound BN-2; the maximum absorption peak is 468nm, the main emission peak is at 485nm, which is blue-green emission, and the half-peak width is 22nm; the energies of S1 and T1 are calculated to be 2.56eV and 2.42eV respectively through the main peak positions of fluorescence and low-temperature phosphorescence, and the ΔE of the two molecules can be calculated ST It is 0.14eV.

[0019] Figure 4 : The external quantum efficiency curve of the electroluminescent device prepared by compound BN-1, the maximum external quantum efficiency is 43.1% (the brightness at this time is 20.7 cd m -2); at a brightness of 1000cd m -2 When the external quantum efficiency is 24.8%, the inset is the electroluminescence spectrum under a driving voltage of 6V. The main peak of the electroluminescence is located at 492nm, which is the emission of blue-green light. It has very high color purity and a half-peak width of 27nm.

[0020] Figure 5 : The external quantum efficiency curve of the electroluminescent device prepared by compound BN-2, the maximum external quantum efficiency is 36.9% (the brightness at this time is 186.0 cd m -2 ); at a brightness of 1000cd m -2 When the external quantum efficiency is 31.8%, the inset is the electroluminescence spectrum under a driving voltage of 6V. The main peak of the electroluminescence is located at 492nm, which is the emission of blue-green light. It has very high color purity and a half-peak width of 28nm. DETAILED DESCRIPTION

[0021] The present invention is further described below in conjunction with the accompanying drawings to facilitate understanding of the present invention by those skilled in the art. Obviously, the described embodiments are only a part of the experiment, not all embodiments, and non-essential modifications, equivalent substitutions and improvements made to the present invention by those skilled in the art according to the above invention content should all be included in the protection scope of the present invention. The raw materials mentioned below are all commercially available or prepared according to known documents or patents, and the process steps and preparation methods not mentioned are all process steps and preparation methods well known to those skilled in the art.

[0022] Example 1: The preparation of BN-1 in this example is as follows:

[0023]

[0024] Synthesis of M1: Under nitrogen protection, 60 mL of anhydrous DMF (N, N-dimethylformamide) solution containing 3,6-di-tert-butylcarbazole (9.8 g, 35.2 mmol) was slowly added dropwise to a mixture of cesium carbonate (13.0 g, 40.0 mmol) and 50 mL of anhydrous DMF within 20 minutes. After the reaction system was stirred at room temperature for 2 hours, 20 mL of anhydrous DMF solution containing 1-bromo-2,6-difluorobenzene (3.1 g, 16.0 mmol) was injected dropwise therein within 15 minutes, and the mixture was heated to 140 ° C and stirred for 24 hours, and then cooled to room temperature. The reaction system was poured into ice water (2000 g), the white solid was filtered out and dried in a vacuum oven, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:3) to obtain a white solid M1 (9.1 g) with a yield of 80%. 1H NMR (500MHz, CDCl3) δ (ppm): 8.16 (d, J = 1.9 Hz, 4H), 7.67 (dd, J = 8.8, 6.6 Hz, 1H), 7.6 1(d,J=8.4Hz,2H),7.51(dd,J=8.6,1.9Hz,4H),7.12(d,J=8.6Hz,4H),1.47(s,36H). 13 C NMR (151 MHz, CDCl3) δ (ppm): 143.03, 139.66, 139.27, 130.86, 129.30, 125.83, 123.81, 123.38, 116.47, 109.40, 34.81, 32.07; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 711.5 and the theoretical value is 711.8.

[0025]

[0026] Synthesis of M2: Under nitrogen protection and ice-water bath, a solution of tert-butyl lithium solution (tert-butyl lithium dissolved in n-pentane solvent, 1.3M, 19.4 mL, 25.2 mmol) in tert-butylbenzene (100 mL) was heated to 60 ° C and stirred for 2 hours, and then boron tribromide (2.4 mL, 25.2 mmol) was added at -30 ° C, and the reaction system was stirred at room temperature for another 1 hour. Finally, N, N-diisopropylethylamine (3.5 mL, 25.2 mmol) was added at 0 ° C, and the reaction system was stirred at 130 ° C for 6 hours and cooled to room temperature. 5 mL of methanol was added to the reaction system to quench the residual boron tribromide. The mixture was extracted with 200 mL of water and 200 mL of dichloromethane, the organic layers were combined, concentrated in vacuo, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:20) to obtain a yellow solid M2 (2.1 g) with a yield of 26%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.12 (d, J = 1.8 Hz, 2H), 8.46 (d, J = 1.7 Hz, 2H), 8.38 (d, J = 8.8 Hz, 2H), 8.3 3–8.24(m,4H),7.99(td,J=8.3,1.3Hz,1H),7.65(dd,J=8.7,2.1Hz,2H),1.67(s,18H),1.53(s,18H). 13C NMR (151 MHz, CDCl3) δ (ppm): 145.24, 144.58, 144.25, 141.54, 138.36, 132.99, 129.79, 127.05, 124.32, 123.65, 123.19, 121.56, 120.62, 117.22, 114.12, 107.93, 35.18, 34.81, 32.21, 31.88; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 640.5 and the theoretical value is 640.7.

[0027]

[0028] Synthesis of M3: Under nitrogen protection, the catalyst methoxy(cyclooctadiene)iridium(I) dimer (43.1 mg, 0.065 mmol) and 4,4'-di-tert-butyl-2,2'-bipyridine (34.9 mg, 0.13 mmol) were added to a solution of M2 (4.20 g, 6.5 mmol) and biboric acid pinacol ester (1.68 g, 6.6 mmol) in ultra-dry tetrahydrofuran (60 mL). The mixture was then bubbled with nitrogen for 5 minutes, heated to reflux and stirred for 24 hours. After cooling to room temperature, the reaction mixture was directly concentrated under reduced pressure, and then further purified by column chromatography using a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:20) to obtain a yellow solid (4.50 g) with a yield of 90%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.14 (d, J = 1.9 Hz, 2H), 8.79 (s, 2H), 8.53 (d, J = 8.8 Hz, 2H), 8.48 (d, J = 1.8 Hz,2H),8.27(d,J=2.0Hz,2H),7.74(dd,J=8.8,2.1Hz,2H),1.67(s,18H),1.54(s,18H),1.49(s,12H). 13 C NMR (151 MHz, CDCl3) δ (ppm): 145.17, 144.55, 143.68, 141.64, 138.48, 129.77, 126.93, 124.59, 123.75, 121.65, 120.75, 117.10, 114.44, 113.77, 84.34, 35.18, 34.82, 32.21, 31.87, 25.09; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 766.8 and the theoretical value is 766.7.

[0029]

[0030] Synthesis of BN-1: Under nitrogen protection, 3-bromobenzothiophene (213 mg, 1 mmol), M3 (766 mg, 1 mmol), K2CO3 (2.76 g, 20 mmol), Pd(PPh3)4 (23 mg, 0.02 mmol) were mixed and added to a 100 mL flask, and then 20 mL toluene and 10 mL water were added, heated to 90 ° C and stirred for 12 hours. After cooling to room temperature, the reaction mixture was poured into water (100 mL), and the reaction mixture was extracted with dichloromethane and water. The organic layers were combined, concentrated in vacuo, and purified by column chromatography with a mixed eluent of dichloromethane / petroleum ether (volume ratio 1:10) to obtain a light yellow solid BN-1 (500 mg) with a yield of 65%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.13 (s, 2H), 8.51 (d, J = 13.6Hz, 4H), 8.43 (s, 1H), 8.39 (d, J = 8.8Hz, 2H), 8.30 (d, J = 1.7Hz, 2H), 8.27–8.21(m,3H),8.08(s,1H),7.74–7.66(m,4H),7.58(t,J=7.3Hz,2H),7.44(t,J=7.4Hz,2H),1.69(s,18H),1.56(s,18H). 13 C NMR (126 MHz, CDCl3) δ (ppm): 145.61, 144.80, 141.87, 141.60, 140.12, 139.46, 138.05, 130.12, 129.68, 129.17, 128.89, 127.20, 126.56, 124.78, 124.05, 123.70, 121.56, 121.02, 120.79, 118.19, 117.45, 114.86, 114.14, 109.41, 106.25, 35.17, 34.84, 32.14, 31.81; Mass Spectrometry MALDI-TOF (m / z) [M + ]: The measured value is 907.1 and the theoretical value is 907.0.

[0031] Example 2: The preparation of BN-2 in this example is as follows:

[0032]

[0033] Synthesis of M4: SeO2 (11.0 g, 0.099 mol) was dissolved in 48% hydrobromic acid (43.0 mL, 0.4 mol) and stirred for 15 minutes; phenylacetylene (5 g, 0.05 mol) and 2-cyclohexene-1-one (4.7 mL) were dissolved in 300 mL of dioxane and slowly added to the mixed solution of SeO2 and hydrobromic acid, reacted overnight and quenched with water. The liquid was extracted with dichloromethane and concentrated to obtain a crude product, which was separated and purified by column chromatography with petroleum ether: dichloromethane (volume ratio 20:1) as the developing solvent to obtain a white solid M4 (6.60 g, yield: 70%). Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 260.1 and the theoretical value is 260.0.

[0034]

[0035] Synthesis of BN-2: Under nitrogen protection, M4 (260 mg, 1 mmol), M3 (766 mg, 1 mmol), K2CO3 (2.76 g, 20 mmol), Pd (PPh3) 4 (23 mg, 0.02 mmol) were mixed and added to a 100 mL flask, and then 20 mL toluene and 10 mL water were added, heated to 90 ° C and stirred for 12 hours. After cooling to room temperature, the reaction mixture was poured into water (100 mL), extracted with dichloromethane and water, the organic layers were combined, concentrated in vacuo, and purified by column chromatography with a mixed eluent of dichloromethane / petroleum ether (volume ratio 1: 10) to obtain a light yellow solid BN-2 (450 mg) with a yield of 55%. 1 H NMR (500MHz, CDCl3) δ (ppm): 9.19 (s, 2H), 8.53 (t, J = 8.0Hz, 4H), 8.37 (d, J = 8.7Hz, 2H), 8.28 (dd, J = 14.1, 7.0Hz, 4H) ,8.14(d,J=7.9Hz,1H),7.62(d,J=8.7Hz,2H),7.55(t,J=7.5Hz,1H),7.52–7.46(m,1H),1.72(s,18H),1.54(s,18H); 13C NMR (126 MHz, CDCl3) δ (ppm): 145.42, 144.76, 144.53, 142.27, 141.74, 140.58, 138.32, 129.86, 127.52, 127.13, 126.36, 125.78, 124.85, 124.54, 123.70, 122.45, 121.72, 120.73, 117.29, 114.18, 108.61, 35.22, 34.81, 32.23, 31.83; Mass spectrum MALDI-TOF (m / z) [M + ]: The measured value is 819.7 and the theoretical value is 819.8.

[0036] The technical effects and advantages of the present invention are demonstrated and verified by applying the compound of the present invention to an organic electroluminescent device to test the actual performance.

[0037] Effect Example 1: Preparation of organic electroluminescent device BN-1

[0038] The technical effects and advantages of the present invention are demonstrated and verified by applying the compounds of the present invention to organic electroluminescent devices to test the actual performance. The specific device preparation process and device performance test experimental operation are as follows: The device preparation process is as follows: Preparation of indium tin oxide (ITO) conductive glass substrate: The substrate is cleaned in ultrasonic bath with deionized water, isopropanol, acetone, toluene, acetone, and isopropanol for 20 minutes each, and dried in an oven; After treating the surface of ITO conductive glass in UV ozone cleaning machine for 40 minutes, it is moved into vacuum evaporation equipment (pressure in the chamber <2×10 -4 Pa); on the anode ITO conductive glass, a hole injection layer HATCN is vacuum-deposited with a thickness of 6 nm; on HATCN, a hole transport layer TAPC is vacuum-deposited with a thickness of 30 nm: on TAPC, an exciton blocking layer TCTA is evaporated with a thickness of 5 nm; on TCTA, an exciton blocking layer mCP is evaporated with a thickness of 5 nm; on mCP, an organic light-emitting layer EML is evaporated with a thickness of 20 nm; on the organic light-emitting layer, an electron transport layer TmPyPB is evaporated with a thickness of 40 nm; on TmPyPB, an electron injection layer LiF is evaporated with a thickness of 1 nm; on LiF, a cathode Al is evaporated with a thickness of 100 nm.

[0039] The structure of the organic electroluminescent device BN-1 is as follows: ITO / HATCN (6nm) / TAPC (30nm) / TCTA (5nm) / mCP (5nm) / EML (20nm) / TmPyPB (40nm) / LiF (1nm) / Al (100nm), where EML represents the light-emitting layer, and the light-emitting layer is composed of a main material PhCzBCz with a mass percentage of 97% and a guest light-emitting material BN-1 with a mass percentage of 3%.

[0040] A direct current voltage was applied to the organic electroluminescent device BN-1 prepared in this example, and the luminescence performance was evaluated using a Spectrascan PR655 luminance meter, and the current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the electroluminescent spectrum, half-peak width, CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), maximum brightness (cd / m 2 The detailed electroluminescent performance data of the device are listed in Table 1. The measured values ​​of the device are as follows: the spectral peak is 492nm, the half-peak width is 27nm, the CIE color coordinates are (0.09, 0.42), the maximum power efficiency is 81.1lm / W and the maximum brightness is 33123cd / m 2 , the maximum external quantum efficiency is 43.1%. When the brightness reaches 100cd / m 2 and 1000cd / m 2 When , the external quantum efficiency can still be maintained at 40.2% and 24.8%.

[0041] Effect Example 2: Preparation of organic electroluminescent device BN-2

[0042] The preparation method is the same as that of Example 1, except that the guest luminescent material BN-1 used in the luminescent layer is replaced by BN-2. The specific device structure is as follows: ITO / HATCN (6nm) / TAPC (30nm) / TCTA (5nm) / mCP (5nm) / EML (20nm) / TmPyPB (40nm) / LiF (1nm) / Al (100nm), EML represents the luminescent layer, and the luminescent layer is composed of 97% by weight of the main material PhCzBCz and 3% by weight of the guest luminescent material BN-2.

[0043] A direct current voltage was applied to the organic electroluminescent device BN-2 prepared in this example, and the luminescence performance was evaluated using a Spectrascan PR655 brightness meter, and the current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescence characteristics, the electroluminescent spectrum, half-peak width, CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), maximum brightness (cd / m 2 The detailed electroluminescent performance data of the device are listed in Table 1. The measured values ​​of the device are as follows: the spectral peak is 492nm, the half-peak width is 28nm, the CIE color coordinates are (0.09, 0.43), the maximum power efficiency is 60.7lm / W and the maximum brightness is 61814cd / m 2 , the maximum external quantum efficiency is 36.9%. When the brightness reaches 100cd / m 2 and 1000cd / m 2 When , the external quantum efficiency can still be maintained at 36.7% and 31.8%.

[0044] Table 1: Data parameters of electroluminescent device provided by the effect embodiment

[0045]

[0046] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A multi-resonance thermally activated delayed fluorescence material based on peripheral heavy atom substitution, the structural formula of which is as follows: Wherein R is S or Se.

2. A multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution as claimed in claim 1, wherein the structural formula is shown as one of the following:

3. Use of a multi-resonance thermally activated delayed fluorescence material based on peripheral heavy atom substitution according to claim 1 or 2 in the preparation of an organic electroluminescent device.

4. The use of a multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution in the preparation of an organic electroluminescent device as claimed in claim 3, characterized in that: The organic electroluminescent device is composed of a cathode, an anode and one or more organic layers between the two electrodes, at least one of the organic layers is an organic light-emitting layer, and the organic light-emitting layer is composed of a multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution prepared according to claim 1 or 2 as a doped guest material and PhCzBCz as a doped host material, and the mass doping ratio of the guest material is 2-5%.

5. The use of a multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution in the preparation of an organic electroluminescent device as claimed in claim 4, characterized in that: The organic electroluminescent device is composed of a transparent substrate, an ITO conductive film anode, a hole injection layer, a hole transport layer, an exciton blocking layer, an organic light-emitting layer, an electron transport layer, an electron injection layer and a cathode layer from bottom to top.

6. Use of a multi-resonance thermally activated delayed fluorescent material based on peripheral heavy atom substitution in the preparation of an organic electroluminescent device as claimed in claim 4 or 5, characterized in that: The electroluminescent device is used for preparing an organic electroluminescent display or an organic electroluminescent lighting source.

Citation Information

Patent Citations

  • Bipolar fluorescent material based on benzo five-membered heterocycle, preparation method of bipolar fluorescent material and organic electroluminescent device

    CN113861172A

  • Boron-containing heteroaromatic ring compound and application thereof

    CN118515694A

  • Thermally activated delayed fluorescent material, organic light-emitting device and display apparatus

    US20230301172A1

Cited By

  • Fused polycyclic compound and electroluminescent device thereof

    CN119390712A